(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Pregnant women are at greatest risk of developing dental disease. According to a number of authors, the prevalence of dental caries during physiological pregnancy is 91.4%, periodontal tissue diseases occur in 90% of cases, damage to teeth that were intact before the carious process is predominantly acute in nature - in pregnant women it is observed in 38% of cases. women (Prokhodnaya V.A. 2015). Secondary caries, exacerbation of the carious process, enamel hyperesthesia occurs in 79% of pregnant women. At the same time, the intensity of the increase in dental caries based on the absolute increase in the caries removal index during pregnancy is 0.83. (Kalinina O.S., 2017).